Trem-2 Promotes Emergence of Restorative Macrophages and Endothelial Cells During Recovery From Hepatic Tissue Damage - Coelho, Inês; Duarte, Nádia; Barros, André; Macedo, Maria Paula; Penha-Gonçalves, Carlos (Frontiers in Immunology, 2021)
Macrophages are pivotal in mounting liver inflammatory and tissue repair responses upon hepatic injury, showing remarkable functional plasticity. The molecular mechanisms determining macrophage transition from inflammatory to restorative phenotypes in the damaged liver remain unclear. Using mouse models of acute (APAP) and chronic (CCl4) drug-induced hepatotoxic injury we show that the immune receptor Trem-2 controls phenotypic shifts of liver macrophages and impacts endothelial cell differentiation during tissue recovery. Trem-2 gene ablation led to a delayed re-population of Kupffer cells correlating with deterred resolution of hepatic damage following acute and chronic injury. During tissue recovery, we found that macrophages transitioning to Kupffer cells expressed high levels of Trem-2. Acquisition of the transition phenotype was associated with a unique transcriptomic profile denoting strong responsiveness to oxidative stress and downmodulation of the pro-inflammatory phenotype, which was not observed in absence of Trem-2. During tissue recovery, lack of Trem-2 favored accumulation of a liver-damage associated endothelial cell population (LDECs), whose transcriptional program was compatible with endothelial de-differentiation. Accordingly, LDECs precursor potential is supported by the downregulation of surface endothelial cell markers and by striking in vitro morphological changes towards typical endothelial cells. In conclusion, we found that the dynamics of liver macrophages in response to liver injury are critically controlled by Trem-2 and this regulation is interlinked with the de-differentiation of endothelial cells and heightened liver pathology. We propose that Trem-2 promotes the transition from pro-inflammatory to tissue repair phase by driving the acquisition of restorative properties in phagocytic macrophages.